Sistem Pendukung Keputusan Siswa/i Yang Berhak Menerima Bantuan Sosial Dengan Menggunakan Metode Decision Table (Studi Kasus SMA Dharma Karya UT Tangerang Selatan) - Ismail Marjuki; Sulasih (CV. Multi Kreasi Media, 2023)
In the provision of social assistance funds currently at SMA Dharma Karya UT, South Tangerang, they still use the manual method, so that the documents that are a requirement for obtaining social assistance funds are not stored properly, making it difficult for the school to track or validate documents, so that there is often an inaccuracy in the recipient of social assistance funds, and when the document is needed the school has to look for the existing documents one by one, so it takes a lot of time to get the one document you are looking for.